2014
DOI: 10.1021/sc500223e
|View full text |Cite
|
Sign up to set email alerts
|

Toward Understanding of Bio-Oil Aging: Accelerated Aging of Bio-Oil Fractions

Abstract: Pyrolysis bio-oil from biomass is a promising intermediate for producing transportation fuels and platform chemicals. However, its instability, often called aging, has been identified as a critical hurdle that prevents bio-oil from being commercialized. The objective of this research is to explore the bio-oil aging mechanism by an accelerated aging test of fractionated bio-oil produced from loblolly pine. When water soluble (WS), ether insoluble (EIS), and pyrolytic lignin (PL) fractions were aged separately, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
78
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 27 publications
1
78
0
Order By: Relevance
“…Aging experiments have been carried out at various research institutions to assess the fuel stability of bio-oil [15,[45][46][47][48][49][50][51][52]. Nevertheless, no standardized methods for measuring the stability of bio-oils are available.…”
Section: Methods To Measure the Stability Of Bio-oilmentioning
confidence: 99%
See 1 more Smart Citation
“…Aging experiments have been carried out at various research institutions to assess the fuel stability of bio-oil [15,[45][46][47][48][49][50][51][52]. Nevertheless, no standardized methods for measuring the stability of bio-oils are available.…”
Section: Methods To Measure the Stability Of Bio-oilmentioning
confidence: 99%
“…Accelerated thermal aging processes have been broadly adopted for thermal stability tests [21,47,48]. In an accelerated thermal aging experiment, the bio-oil is stored at an elevated temperature for a certain time, and the physical and chemical properties prior to and after the aging process are analyzed [53].…”
Section: Thermal Stability Test Methodsmentioning
confidence: 99%
“…Owing to the predominance of thermally stable chemical groups, TGRP oil distills with high yields of dry organic non-acidic products (∼60-65%) and significantly less residual bottoms, analogous to heavy vacuum gas oil (HVGO) or vacuum residuum. The 65% yield is a significantly better performance than when traditional bio-oil is distilled (<20% dry organic yield), where excessive repolymerization of the pyrolytic lignin occurs [7,8], resulting in more than 40 wt% of the bio-oil left as bottoms. In both cases, a significant residuum fraction necessitates downstream fractionation or conversion into lighter compounds.…”
Section: Introductionmentioning
confidence: 99%
“…As far as thermal stability is concerned, a few studies on the chemical changes of biomass-pyrolysis bio-oil stored at elevated temperatures (up to 90°C) over extended periods of time (up to 1 week) using different methodology can be found in the literature [3,4,[6][7][8][9][10][11][12]. Boucher et al [7], Hilten et al [3] and Samanya et al [8] argued that 80°C was a suitable temperature for testing thermal stability since, at this temperature, rather large change in the properties of biomass-pyrolysis biooil can be expected.…”
Section: Introductionmentioning
confidence: 99%
“…Further important properties to study are the variations in the chemical structural changes (gas chromatography-mass spectrometry (GC-MS) and nuclear magnetic resonance (NMR)) and the molecular weight (Mw) during ageing. It has also been shown to be very beneficial to apply a fractionation approach when studying reaction mechanisms and chemical structural changes in bio-oil because it is much more representative of the actual reaction environments than model compounds [11]. According to these authors, the water-insoluble fraction (pyrolytic lignin fraction) showed a significant increase in Mw after accelerated ageing at 80°C and that a higher increase was obtained with a higher ageing temperature (110°C).…”
Section: Introductionmentioning
confidence: 99%